THE OVERVIEW OF CLERKSHIP STUDENTS OF THE FACULTY OF MEDICINE AND HEALTH SCIENCES AT KRIDA WACANA CHRISTIAN UNIVERSITY YEAR 2022 AWARENESS TOWARDS REFRACTIVE ERROR - Santi Anugrahsari; Robert Tupan us Abatan; Tengku Nadira Munawarah Tengku Adnan; Lena Mariana; Nadya Gabriella Susanto; Ester Cesaria Claudia Sosomar (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Background Knowledge of medical science is essential to basic medical clerkship students who should prepare for a clinical clerkship. Eye disease is still one of the biggest health problems globally, especially those which cause blindness, one of which is related to refractive disorders. Purpose This study aims to explore knowledge about refractive abnormalities to basic medical clerkship students of UKRIDA in 2022. Method It employs a descriptive research method, and the questionnaires are created based on a Likert scale and shared on Google Forms. Result The number of participants is 80 people with an age range of 20-25 years with 67.5% of women. A total of 43.75% of students have a good level of knowledge, and 56.25% of them hold a sufficient level of knowledge about refractive disorders. Meanwhile, 86.25% of them have a good understanding about eye anatomy and refractive examination. 75.75% have a good level of knowledge about myopia. 32.5% have a good level of knowledge about hypermetropia. And, as many as 35% students have a good understanding of astigmatism. Further, a total of 37.5% of students have a good level of knowledge about refractive anomalies. Conclusion A total of 43.75% of students have a good level of knowledge, and 56.25% have a sufficient level of knowledge about refractive disorders. Age, education level, environmental factors, and social factors influence refractive conditions. Keywords: knowledge, refractive abnormalities, clinical clerkship student